Abuse and misuse of tramadol in patients with non-oncologic pain in a region of Southern Europe - M. Perelló; K. Rio-Aigé; G. Cereza; P. Rius; F. J. Pérez-Cano; M. Rabanal (Journal of Pharmaceutical Policy and Practice)
Background Tramadol can cause dependence even within the recommended dose range. Its use has increased recently, especially in patients with chronic pain, and although a growing body of literature identifies a non-therapeutic use, patterns of misuse of tramadol is so far limited.Methods Two-year observational and cross-sectional study (January 2020 - December 2021) was conducted in 75 community pharmacies from Catalonia. To estimate the potential abuse and misuse of tramadol by patients visiting community pharmacy, and to establish the demographic characteristics of the tramadol users, a validated questionnaire based on the Finch criteria was designed. A total of 251 cases were registered.Results Data show that women were more involved (56.6%) and the highest proportion was found in the age interval of 46-65 years (42.6%). The combination of tramadol and paracetamol was reported in 54.6% of the cases and 73.7% corresponded to immediate-release tablets. In 93.6% of the cases, the request was preceded by previous use. Conversely, young men showed a higher non-prescription request for tramadol, reporting acute pain (p < 0.05). These results indicate that there is non-therapeutic use among patients who visit community pharmacies for information on two profiles.Conclusion This study shows that being an aged woman and suffering from chronic pain seems to involve a risk of generating dependence on tramadol. Likewise, a suspicion of recreational use of tramadol by young people has also been identified. There is a need to investigate how to manage chronic pain, given its complexity and take into account the risk of misuse that may come with tramadol. The involvement of characteristics such as gender as well as the pharmaceutical form in the development of tramadol misuse also needs to be analysed deeply. It is mandatory to evaluate the criteria for prescribing tramadol and initiatives to improve the knowledge of the health professionals and the population.